2016
DOI: 10.1016/j.jmb.2015.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Coupling between Histone Conformations and DNA Geometry in Nucleosomes on a Microsecond Timescale: Atomistic Insights into Nucleosome Functions

Abstract: An octamer of histone proteins wraps about 200 base pairs of DNA into two super-helical turns to form nucleosomes found in chromatin. Although the static structure of the nucleosomal core particle has been solved, details of the dynamic interactions between histones and DNA remain elusive. We performed extensively long unconstrained, all-atom microsecond molecular dynamics simulations of nucleosomes including linker DNA segments and full-length histones in explicit solvent. For the first time we were able to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
158
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(174 citation statements)
references
References 89 publications
16
158
0
Order By: Relevance
“…Instead, these results suggest that there is a level of regulation of histone acetylation that is independent of HAT recruitment. Molecular simulation studies predict histone tails to be tightly intertwined with nucleosomal DNA (Li and Kono 2016;Shaytan et al 2016), and thus disruption of these interactions may be required for acetylation by available HATs. Interestingly, although RNAPII is also found across gene bodies, NET-seq and photoactivatable ribonucleosideenhanced cross-linking and IP experiments show that RNAPII struggles to transcribe through the 59 ends of genes (Churchman and Weissman 2011;Schaughency et al 2014), where the majority of histone acetylation is found.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, these results suggest that there is a level of regulation of histone acetylation that is independent of HAT recruitment. Molecular simulation studies predict histone tails to be tightly intertwined with nucleosomal DNA (Li and Kono 2016;Shaytan et al 2016), and thus disruption of these interactions may be required for acetylation by available HATs. Interestingly, although RNAPII is also found across gene bodies, NET-seq and photoactivatable ribonucleosideenhanced cross-linking and IP experiments show that RNAPII struggles to transcribe through the 59 ends of genes (Churchman and Weissman 2011;Schaughency et al 2014), where the majority of histone acetylation is found.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, atomistic simulations have already provided structural insight into the transient DNA unwrapping near its entry/exit sites, [21][22][23] and revealed the effect of post-translational modifications and different histone variants on nucleosomal dynamics. 22,24 The minimal systems are large in size, and involve a complex ensemble of molecular players having intricate physicochemical interactions.…”
Section: Coarse-grained Protein-dna Modelmentioning
confidence: 99%
“…We use, to our knowledge, a novel approach-a combination of modern molecular modeling techniques (33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46) and atomic force microscopy (AFM) measurements-to add experimentally consistent models of these three new members to the family of atomistic structures of the nucleosome particles. …”
Section: Introductionmentioning
confidence: 99%